Determinan Tindakan Fraud pada Perguruan Tinggi - Arifah, Alfin Nisaul; Laksmi, Ayu Chairina (Jurnal Akuntansi dan Bisnis, 2025)
This study aims to examine the factors influencing fraud in University. These factors include compensation suitability, internal control effectiveness, whistleblowing system, organizational culture, and religiosity. The study was conducted at the Top 27 universities in the Special Region of Yogyakarta according to UniRank 2024. The quantitative approach used was a survey method by distributing questionnaires to 165 university employees with at least one year of work experience. The analytical method used was multiple linear regression analysis. This study employed fraud triangle theory as its theoretical framework.. The results showed that compensation suitability, internal control effectiveness, and religiosity had no effect on the occurrence of fraud in higher education. Meanwhile, the whistleblowing system and organizational culture had a negative and significant influence on the occurrence of fraud in University.